2019
DOI: 10.1212/wnl.0000000000008081
|View full text |Cite
|
Sign up to set email alerts
|

High-precision plasma β-amyloid 42/40 predicts current and future brain amyloidosis

Abstract: ObjectiveWe examined whether plasma β-amyloid (Aβ)42/Aβ40, as measured by a high-precision assay, accurately diagnosed brain amyloidosis using amyloid PET or CSF p-tau181/Aβ42 as reference standards.MethodsUsing an immunoprecipitation and liquid chromatography–mass spectrometry assay, we measured Aβ42/Aβ40 in plasma and CSF samples from 158 mostly cognitively normal individuals that were collected within 18 months of an amyloid PET scan.ResultsPlasma Aβ42/Aβ40 had a high correspondence with amyloid PET status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
707
4
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 644 publications
(765 citation statements)
references
References 49 publications
46
707
4
8
Order By: Relevance
“…More recently, studies using a more sensitive IP-MSp method detected a decreased Aβ 42 /Aβ 40 ratio in plasma and reported a diagnostic accuracy of almost 90% of plasma Aβ 42 /Aβ 40 ratio in predicting Aβ PET positivity in AD, MCI and cognitively normal states [110]. Similar results have been presented by other groups [111,112].…”
Section: Mass Spectrometrysupporting
confidence: 64%
“…More recently, studies using a more sensitive IP-MSp method detected a decreased Aβ 42 /Aβ 40 ratio in plasma and reported a diagnostic accuracy of almost 90% of plasma Aβ 42 /Aβ 40 ratio in predicting Aβ PET positivity in AD, MCI and cognitively normal states [110]. Similar results have been presented by other groups [111,112].…”
Section: Mass Spectrometrysupporting
confidence: 64%
“…Brain A␤ antemortem is quantifiable via radioactive labelling on positron emission tomography (PET) [6] and can also be estimated from A␤ concentrations in cerebrospinal fluid (CSF) as a molecular biomarker [7]. Amyloid PET and CSF A␤ can be used interchangeably for clinical diagnosis [7,8] and are increasingly relied upon in diagnostic frameworks [9,10]. Both have also been shown to predict future cognitive decline [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated methods for A␤ analysis have been developed in recent years, but results from the first diagnostic and epidemiological applications of these methods have been inconsistent. A number of studies have found an association of lower plasma A␤ concentrations (thought to reflect a greater brain A␤ burden) with more severe neuropsychological deficits [23,24], with an increased risk of developing AD [25,26], and with amyloidpositive PET [8,27,28] or amyloid-abnormal CSF [29,30] as current gold standards for AD diagnosis. Others report results in the opposite direction [31][32][33][34] and null findings, too, are frequent [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this is the first study to offer PET examination seven years post-stroke, and by that adding important knowledge to amyloid evaluation post-stroke. Studies have shown that plasma Aβ42/Aβ40 levels accurately determine amyloid PET status in cognitively normal research participants (72), and, therefore, might be more feasible in a post-stroke population, both due to antithrombotic medication, CI and low PET attendance in most studies so far.…”
Section: Discussionmentioning
confidence: 99%